Deliberate : while you are asleep - See Toh, Gel Jia Yao (2014)
I am interested in the manner people spend their waking hours while many others are asleep. Primarily, I want to investigate nocturnal humans and early-risers in their activities, the activeness of their state of mind, and the cause of their presence in the dark of night. To address this project in a systematic manner, I intend to investigate the presence of activities in the domestic environment, and on the streets. Through careful selection, I sought to produce imagery that will provoke discussion about the state of nightlife and sleep-deprivation in this city-state. By taking advantage of dancing shadows, chance encounters, available light and strategically placed strobes, I hope to question what it is that keeps us awake.